(untitled) (Journal of Economic Research & Business Administration, 2016)
In article questions on decrease in tax risk within management ac-counting are considered. The main characteristics inherent in tax risk are defined behavior models of taxpayers are allocated. The author studied interrelation of tax planning and tax risk and defined its special value for decrease in tax risk. In article modern problems on management of tax risks of the company, as integral part in the general system of adoption of administrative decisions are considered. Need of the organization of scientific researches, uses of various methods of decrease in tax risks at the enterprise, development of strategy of management of risk, in the form of forecasting of risks locates. Functions of tax risk are defined and measures for their account, for the purpose of decrease in tax risks are offered. The basic principles of an assessment of tax risks connected with the concept of the acceptable risk, determination of threshold values of risk, calcu-lation of size of economic damage of the indicators necessary for a risk management are opened.